Interreligious Inheritance: Exploring The Fatwa of The Indonesian Scholar Number 5/MUNAS VII/MUI/9/2005 on Interreligious Inheritence - Indah Rahmahdaniyati; Lisnawati (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
Religious differences become a barrier to inheritance. Islam stipulates that Muslims only inherit from Muslims. The Indonesian Council of Ulama, which accommodates Islamic scholars, zu'ama, and intellectuals in Indonesia to guide, foster, and protect Muslims throughout Indonesia, on 21 Jumadil Akhir 1426 H/ 28 July 2005 M issued a fatwa regarding interfaith inheritance. The research method uses a normative method and a critical discourse analysis approach proposed by Norman Fairclough regarding the Dialectical Relational Approach (DRA). The results of the study stated that the MUI fatwa is in line with the opinions that explain that Muslims do not inherit non-muslims. However, the fatwa still allows non-muslims to get a share of the inheritance, namely through grants, wills or gifts. The Indonesian Council of Ulama Fatwa Number: 5/MUNASVII/MUI/9/2005 concerning Interfaith Inheritance is one of the progressive products of Islamic law. The Indonesian Council of Ulama always responds quickly to all legal problems in society, including interfaith inheritance.